TEPUNG BEKICOT (Achatina fulica) SEBAGAI PAKAN TAMBAHAN UNTUK MENINGKATKAN KUALITAS SEMEN DOMBA (Ovis aries) - Jayanti Berliana Dewi; Delvi Ramadayani; Marchellia Dhiafifah Wahyunandha; Melati Kusuma Bunda Pertiwi; Sri Gustari; Topas Wicaksono Priyo Jr (Jurnal Sain Veteriner, 2022)
One of the effort to provide superior rams is to pay attention to the provision of feed that has good substances and is able to improve the quality of sperm. Based on studies, snail flour has a fairly high protein content and snails can be an alternative source of protein in additional feed. This study aims to improve the quality of sheep sperm using an additional feed of snail flour (Achatina fulica) which can increase the use value and economic value. Eight sheep used in this research were divided into one group as the control and two groups as the treatment. The control group was given standard sheep forage, while the treatment groups were given standard sheep forage added with flour snail of 5% and 10%. Sperm collection using castration method. Parameters observed were motility, viability, and concentration of sperms. The results of the study showed that the addition of snail flour as additional feed for sheep affected sperm quality with a significant increase in concentration parameters, while motility and viability did not show a significant increase